Organization development : a practitioner's tool kit - Ralphs, Lenny T. (Crisp Pub. Menlo ParkUS, 1996)
Defines and explains organization development (OD) and advises on selection of OD consultants - their role, contracts etc. Provides models and methods for OD, for example, diagnostic models, data collection methods. Examines change and proposes psychological strategies for managing change.